Screening for okra enation leaf curl disease resistance in wild okra (Abelmoschus moschatus ssp. moschatus) germplasm of India - KUMARI, POOJA; SINGH, S P; GANGOPADHYAY, K K; CHALAM, V C; DUBEY, S C; RANJAN, PRAGYA (The Indian Journal of Agricultural Sciences, 2021)
Okra enation leaf curl disease (OELCuD) caused by Okra enation leaf curl virus (OELCuV) is a whitefly (Bemisia tabaci) transmitted viral disease of okra which deteriorates vegetable quality and reduces yield. The OELCuV was confirmed based on the amplicon of 1.3 Kb of beta satellite (DNA-Î²) molecule of the virus. Field screening of wild okra (Abelmoschus moschatus ssp. moschatus) accessions was carried out for OELCuD resistance during kharif 2017-19 at experimental Farm of ICAR-National Bureau of Plant Genetic Resources, Pusa, New Delhi. Out of 76 wild okra accessions tested, 10 accessions, viz. EC360586, EC360794, EC360830, EC360900, EC359730, EC359836, EC359870, EC360351, EC361111 and EC361171 showed resistant (R) reaction in kharif 2017, whereas in kharif 2019, only four accessions, viz. EC360794, EC360586, EC360830 and EC361171 exhibited R reaction and remaining six accessions were moderately resistant (MR). In the first year, average percent disease index (PDI) was 14.15 and overall PDI ranged from 3.70 to 52.86. The range of PDI was 4.53-56.40 during the second year with an average PDI value 18.04. Apart from PDI determination, whitefly population was also monitored in both the years mainly showed moderate preference. The prominent four accessions of okra, viz. EC360794, EC360586, EC360830 and EC361171 could be utilized in resistance breeding programmes against OELCuV.